APLIKASI PENGELOLAHAN DOKUMEN PIDANA PENGADILAN NEGERI TONDANO KELAS IB BERBASIS WEB - Saknohsiwy, Lorida Julensa Holiba; kembuan, Olivia; Santa, Kristofel (Program Studi Teknik Informatika, 2023)
Abstract— The criminal document management application is designed to assist in the delivery of court decision excerpts, the scheduling of court sessions, the detention of the court chairperson, and the detention of judges from the Tondano District Court to the Prosecutor's Office (Minahasa, Tomohon, South Minahasa), Correctional Institutions (Minahasa, Tomohon, South Minahasa), and the delivery of search warrant decisions, extension of detention permits, and seizure permits to the Police (Minahasa, Tomohon, Southeast Minahasa). The purpose of this research is to design, build, and develop a web-based criminal document management application at the Tondano District Court, aiming to facilitate employees in managing and delivering each case decision efficiently. This system aims to provide fair legal services to seekers of justice. The criminal document management application utilizes extreme programming methodology and the CodeIgniter framework. The programming language used is PHP, and MySQL serves as the database. Access to this application is restricted to administrators appointed by the criminal junior clerk of the Tondano District Court, the Prosecutor's Office administrator, the Police administrator, and the Correctional Institution administrator.